Environmental Factors Influencing Chlorophyll-a Concentration in Tri An Reservoir, Vietnam - Thi Hoang Yen, Tran; Thai, Tran Thanh; Van Tu, Nguyen; Xuan Quang, Ngo; Thanh Luu, Pham (VNU Journal of Science: Earth and Environmental Sciences; Vol 37 No 2DO - 10.25073/2588-1094/vnuees.4535, 2021)
Chlorophyll-a (Chl-a) has been used extensively as an essential indicator of trophic state in the assessment and monitoring of surface water quality environments. The environmental factors can influence Chl-a concentrations; thus, to determine the relationship between Chl-a concentration and factors. The research was carried out in dry season (March 2016) and wet season (September 2016) in Tri An reservoir, Dong Nai Province, Vietnam and performed by Spearman's correlation analysis and Linear regression analysis. The result showed that Chl-a varied between 12.84 and 783.51 µg/L and was quite different a cross stations in two surveys. Factor analysis and the best models revealed the association of strong physico-chemical with Chl-a concentration. The Chl-a was significantly positively correlated with Total Suspended Solids (TSS) and negative with Nitrate (NO 3 - ) in the dry season, while in the wet season the positive relationships between Chl-a concentration and Dissolved Oxygen (DO), Temperature and a strong negatively correlated with Phosphate (PO 4 3- ) correlation were found. This relationships inferred that the nutrients brought by the influx of reservoir into the study area have contributed to control the growth and abundance of phytoplankton. Thus, the importance of environmental factors in structuring Chl-a concentration may be used to guide the conservation of the aquatic ecosystems in the reservoir.